Police Action and the State-Created Danger Doctrine: a Proposed Uniform Test - Eisenhauer, Christopher M. (2016)
The state-created danger doctrine provides the basis for a potential claim when a state actor creates a danger that results in an injury to the plaintiff. The doctrine may be interpreted as an exception to the general rule that a state has no duty to protect one private citizen from another. Because the U.S. Supreme Court has not addressed the issue, many variations of the state-created danger doctrine exist across the federal circuits. The resulting lack of uniformity has led to inconsistent results, promoting unfairness for litigants throughout the country. This Comment explores the history, objectives, and current approaches to the state-created danger doctrine. This Comment also examines the public policy considerations with which the federal circuits seem to struggle. A recent case involving police action demonstrates the perils of inconsistency and the need for balance to further the interests of the public. Finally, this Comment recommends a simplified uniform test to restore uniformity to the federal circuits